2022
DOI: 10.1007/s12551-021-00924-4
|View full text |Cite
|
Sign up to set email alerts
|

Dissecting cricket genomes for the advancement of entomology and entomophagy

Abstract: Significant advances in biophysical methods such as next-generation sequencing technologies have now opened the way to conduct evolutionary and applied research based on the genomic information of greatly diverse insects. Crickets belonging to Orthoptera (Insecta: Polyneoptera), one of the most flourishing groups of insects, have contributed to the development of multiple scientific fields including developmental biology and neuroscience and have been attractive targets in evolutionary ecology for their divers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 139 publications
(169 reference statements)
1
11
0
Order By: Relevance
“…A quick comparison of the length of the BUSCO reference gene sequences estimated that the A. domesticus genes were on average 80% longer than those in T castaneum. We also noticed that, in most cases, the longer genes were due to longer introns that may be due to TEs as has been observed in other Orthoptera [ 53 , 54 ]. Therefore, we compared repetitive elements in the A. domesticus genome assembly with those available for other orthopterans and found that the A. domesticus genome assembly contains the highest content of TEs (almost half of the assembly) compared to other cricket genomes.…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…A quick comparison of the length of the BUSCO reference gene sequences estimated that the A. domesticus genes were on average 80% longer than those in T castaneum. We also noticed that, in most cases, the longer genes were due to longer introns that may be due to TEs as has been observed in other Orthoptera [ 53 , 54 ]. Therefore, we compared repetitive elements in the A. domesticus genome assembly with those available for other orthopterans and found that the A. domesticus genome assembly contains the highest content of TEs (almost half of the assembly) compared to other cricket genomes.…”
Section: Discussionsupporting
confidence: 70%
“…Because repetitive elements, in particular transposable elements (TEs), are well-known contributors to genome size expansion in a wide range of insect species [ 53 , 54 ], we further examined the relative contribution of repetitive elements to the genome sizes of the orthopteran species. There was a significant correlation between total contents of repetitive elements and genome sizes in Orthoptera species ( p = 0.024 and R2 = 0.61) ( Figure S6a ).…”
Section: Resultsmentioning
confidence: 99%
“…A quick comparison of the length of the BUSCO reference gene sequences estimated that the A. domesticus genes were on average 80% longer than those in T castaneum. We also noticed that, in most cases, the longer genes were due to longer introns that may be due to TEs as has been observed in Orthoptera [7273]. Therefore, we compared repetitive elements in the A. domesticus genome assembly with those available for other orthopterans and found that the A. domesticus genome assembly contains the highest content of TEs (almost half of the assembly) compared to other cricket genomes.…”
Section: Discussionmentioning
confidence: 87%
“…For example, in the cricket genomes, L. kohalensis LINE had the highest abundance at 13.4%, while G. bimaculatus and T. oceanicus had only 3.34% and 4.04% LINE, respectively. Because repetitive elements, in particular transposable elements (TEs), are well-known contributors to genome size expansion in a wide range of insect species [72][73], we further examined the relative contribution of repetitive elements to the genome sizes of the orthopteran species. There was a significant correlation between total contents of repetitive elements and genome sizes in Orthoptera species (P=0.024 and R 2 = 0.61) (Figure S6a).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation